(untitled) (Research, Society and Development, 2021)
Introduction: Critically ill patients diagnosed with COVID-19 require a prolonged period of hospitalization, thus generating the deleterious effects of immobility. Muscle weakness is noticed in the first days of hospitalization and may progress to functional incapacity. Therefore, physical therapy intervention should be started early, promoting the functional recovery of these individuals as soon as possible. Therefore, the aim of this study was to describe the frequency of early mobilization in critically ill patients. Method: It is a descriptive and retrospective study. Sample composed of patients diagnosed with COVID-19, hospitalized for more than 24 hours and on mechanical ventilation. Data collection started after approval by the Research Ethics Committee, performed through medical records and then tabulated in a Google spreadsheet and analyzed using descriptive statistics. Results: All individuals included were mobilized during their hospital stay, most of them men and over 50 years of age. Passive mobilization was the most performed (34.4%) when compared to other types of exercises. Conclusion: Patients received early physical therapy intervention. And the physiotherapist is increasingly essential and recognized in the recovery of these patients.